Stenosis effects on the fluid mechanics of the common carotid artery bifurcation for unsteady flows - Antonova, Nadia; Xu, D.; Velcheva, I.; Kaliviotis, Efstathios; Tosheva, P. (My University, 2015)
The time-varying blood flow in the common carotid artery (CCA) bifurcation is numerically studied on the basis of Navier-Stokes equations for four different cases, including cases with stenoses at different sites in the vicinity of the bifurcation. The cases studied were: (a) without stenoses, (b) with one stenosis upstream the bifurcation, (c) with two opposite stenoses upstream the bifurcation and (d) with an additional stenosis on the apex of the bifurcation. The mesh was generated via a geometry reconstruction and imported into a computational fluid dynamics (CFD) solver. The numerical results of the blood flow in the CCA bifurcation gave a detailed picture of the axial velocity and presented as velocity and vorticity magnitudes. More specifically, it was observed that the appearance of stenotic regions upstream the bifurcation affect both the velocity and vorticity characteristics, whereas a stenoses on the apex of the bifurcation seems to have a small effect on the vorticity characteristics downstream the flow.
Keywords: 3D numerical calculations; CCA bifurcation; Stenosis; Velocity and vorticity magnitude